Carboxymethyl Cellulose from palm oil empty fruit bunch – their properties and use as a Film Coating Agent - Amin M.C.I; Soom R.M; Ahmad I.; Lian H.H (penerbit ukm, 2006)
This study was carried out to determine the physicochemical properties of carboxymethyl cellulose (CMC) derived from cellulose of palm oil empty fruit bunch (EFB) and its use asa film-coating agent. Samples were prepared at various concentrations and then their physicochemical properties were studied including the viscosity, pH, tensile strength of films, surface properties of the films and dissolution studies on coated tablets. CMC EFB showed lower viscosity than commercial CMC product at the concentration of 1%, 2% and 3% with the values of 44.0cp, 299.9cp, 358.9cp and 90.0cp, 689.9cp, 5569.0cp respectively. The tensile strength of the films for CMC EFB were 7.85MPa, 14.79MPa, 10.36MPa while the commercial CMC exhibited higher values of 21.72MPa, 35.14MPa and 26.9MPa at similar concentration. The scanning electron microscope showed different surface properties of the films for both of them where the commercial CMC is smoother in texture and very transparent unlike its counterpart. However, dissolution studies on paracetamol tablets coated using the samples showed no significant difference (p>0.05) in drug release profile between the two materials. Hence, CMC EFB has a greater potential to be developed as a competitive tablet-coating agent despite the differences in its physicochemical properties.